STRATEGI PENGENDALIAN PENCEMARAN MERKURI DARI PERTAMBANGAN EMAS RAKYAT DI SUNGAI POBOYA, KOTA PALU YANG BERKELANJUTAN - Muhammad - Aswadi (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2019)
ABSTRACTPoboya River has provide many benefits for local as to suffice their needs of clean water, agriculture/ plantation, husbandry, household and also used for people’s gold mining. Gold mining is dominated by amalgamation techniques which are potentially contaminated by mercury. This study aims to derive a mercury pollution control strategy from a sustainable people’s gold mining. This study includes interviewing the key stakeholders that have been chosen purposively using questionnaire. The data obtained were then analyzed by AHP. The results of this study found that potential factors on mercury pollution control were government policies which related to the implementation of gold mining management, supporting facilities and infrastructure, and the adequate level of community education. The main stakeholders who had the control should be hold by the government (local government), law enforcers and the community. Preferred objectives should be to reduce the pollution and to restore the ecosystem.  The ideal strategy for mercury pollution control from the gold mining process become successful and sustainable are super minor technology that uses the density without adding hazardous and toxic materials.